Handbook of Medical Image Computing and Computer Assisted Intervention - Zhou, S. Kevin; Rueckert, Daniel; Fichtinger, Gabor (Elsevier Science & Technology, 2019)
Handbook of Medical Image Computing and Computer Assisted Intervention presents important advanced methods and state-of-the art research in medical image computing and computer assisted intervention, providing a comprehensive reference on current technical approaches and solutions, while also offering proven algorithms for a variety of essential medical imaging applications. This book is written primarily for university researchers, graduate students and professional practitioners (assuming an elementary level of linear algebra, probability and statistics, and signal processing) working on medical image computing and computer assisted intervention.